2020
DOI: 10.1007/s42452-020-03895-5
|View full text |Cite
|
Sign up to set email alerts
|

A new memetic global and local search algorithm for solving hybrid flow shop with multiprocessor task scheduling problem

Abstract: Hybrid flow shop (HFS) scheduling problem is combining of the flow shop and parallel machine scheduling problem. Hybrid flow shop with multiprocessor task (HFSMT) scheduling problem is a special structure of the hybrid flow shop scheduling problem. The HFSMT scheduling is a well-known NP-hard problem. In this study, a new memetic algorithm which combined the global and local search methods is proposed to solve the HFSMT scheduling problems. The developed new memetic global and local search (MGLS) algorithm con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As the study by Yeung et al (2004) sets the due window at the center of C max found by Johnson’s rule, where the both ends of time window e and d equal to (0.4 ×C max ) and (0.6× C max ), respectively, we adopted the same approach in our research; however, we used C max values found previously in our study (Engin, 2016) to determine the earliest and latest times of common due window. If a job is completed before the time e , earliness penalty will incur, and if a job is completed after the time d , tardiness penalty will incur, and if a job is completed between the common due window, no penalty will incur.…”
Section: Developed Memetic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…As the study by Yeung et al (2004) sets the due window at the center of C max found by Johnson’s rule, where the both ends of time window e and d equal to (0.4 ×C max ) and (0.6× C max ), respectively, we adopted the same approach in our research; however, we used C max values found previously in our study (Engin, 2016) to determine the earliest and latest times of common due window. If a job is completed before the time e , earliness penalty will incur, and if a job is completed after the time d , tardiness penalty will incur, and if a job is completed between the common due window, no penalty will incur.…”
Section: Developed Memetic Algorithmmentioning
confidence: 99%
“…The parameter set used in this study is given in Table IV. This parameter set is formed by Full Factorial Design implemented in the study (Engin, 2016). The penalties per unit time of earliness α j and β j tardiness which are taken 1 for all jobs for the simplicity, since the focus in this study is on developing earliness and tardiness minimization for the first time and to see if the local search approach makes any significant difference.…”
Section: Computational Experimentsmentioning
confidence: 99%